Alterations in Serum Biochemical Parameters of Horses with Leptospirosis - Guzel, S.; Tanriverdi, M. (Asian Journal of Chemistry, 2013)
In this study, the alterations in serum biochemical parameters of horses with leptospirosis was investigated. For this aim, 8 h with leptospirosis, were determined by the microscopic agglutination test and 8 healthy horses were used as material. The levels of serum glucose, urea, creatinine, uric acid, total cholesterol, high-density lipoprotein (HDL), triglyceride, total protein, albumin, globulin, aspartate aminotransferase (AST), alkaline phosphatase (ALP), lactate dehydrogenase (LDH), creatinine kinase (CK), sodium, potassium, chloride, calcium, phosphorus, magnesium were evaluated in leptospirosis cases and healty horses. Although we found significant decreases in levels of glucose (p < 0.01), uric acid (p < 0.01), HDL cholesterol (p < 0.05), ALP (p < 0.01), Cl (p < 0.01), Ca (p < 0.05), P (p < 0.001) in horses with leptospirosis, level of urea (p < 0.05) in horses with leptosprosis showed significant increases. The results obtained may suggest that these parameters might have taken part in the diagnosis and treatment of horse leptospirosis.